Hybrid machine learning algorithms to predict condensate viscosity in the near wellbore regions of gas condensate reservoirs - Behesht Abad, Abouzar Rajabi; Mousavi, Seyedmohammadvahid; Mohamadian, Nima; Wood, David A.; Ghorbani, Hamzeh; Davoodi, Shadfar; Alvar, Mehdi Ahmadi; Shahbazi, Khalil (Journal of natural gas science and engineering, 2021)
Gas condensate reservoirs display unique phase behavior and are highly sensitive to reservoir pressure changes. This makes it difficult to determine their PVT characteristics, including their condensate viscosity, which is a key variable in determining their flow behavior. In this study, a novel machine learning approach is developed to predict condensate viscosity in the near wellbore regions (μc) from five input variables: pressure (P), temperature (T), initial gas to condensate ratio (RS), gas specific gravity (γg), and condensate gravity (API). Due to the absence of accurate recombination methods for determining μc machine learning methods offer a useful alternative approach. Nine machine learning and hybrid machine learning algorithms are evaluated including novel multiple extreme learning machine (MELM), least squares support vector machine (LSSVM) and multi-layer perceptron (MLP) and each hybridized with a particle swarm optimizer (PSO) and genetic algorithm (GA). The new MELM algorithm has some advantages including 1) rapid execution, 2) high accuracy, 3) simple training, 4) avoidance of overfitting, 5) non-linear conversion during training, 6) no trapping at local optima, 6) fewer optimization steps than SVM and LSSVM. Combining MELM with PSO, to find the best control parameters, further improves its performance. Analysis indicates that the MELM-PSO model provides the highest μc prediction accuracy achieving a root mean squared error (RMSE) of 0.0035 cP and a coefficient of determination (R2) of 0.9931 for a dataset of 2269 data records compiled from gas-condensate fields around the world. The MELM-PSO algorithm generates no outlying data predictions. Spearman correlation coefficient analysis identifies that P, γg and Rs are the most influential variables in terms of condensate viscosity based on the large dataset studied. •2269 viscosity data records compiled from worldwide gas condensate fields.•Machine learning with optimizers reliably predicts condensate viscosity (μc).•Empirical models do not accurately predict μc and are not fit for purpose.•MELM-PSO model yields best μc predictions outperforming other models.•Pressure, gas gravity and condensate/gas ratio have greatest influence.